PENGARUH PENGGUNAAN JENIS BAHAN PENGGUMPAL LATEKS TERHADAP MUTU SIR 20 - Ganif Hidayoko; Okta Wulandra (UNIVED Press, Universitas Dehasen Bengkulu, 2014)
Indonesia is the number two country 's that produce of natural rubber in the world after Thailand. The main drawback of natural rubber when compared to synthetic rubber is in the consistency of its quality. The aim of this research is to determine the effect of coagulant agent : alum, acetic acid and TSP ( Triple Super Phosphate ) on the ash content and the value of plasticity retention index ( PRI ) of SIR 20 ( Standard Indonesian Rubber ). Research conducted two (2 ) stages, namely the stage of processing rubber SIR 20 with latex base material. Clots made with latex coagulant treatment variations, which alum, acetic acid and TSP. Once formed rubber SIR 20, then analyzed ash content and value analysis PRI. The experimental design used was a factorial design experiment with a single factor, namely the type of coagulant consisting of a 20 % solution of TSP, 20 % alum solution and 20 % acetic acid solution with three times repetition of treatment, if there is a real difference, then tested further by DMRT. The results showed that the use of acetic acid coagulant and alum produce rubber SIR 20 with ash content and PRI value that meets the standards set by SNI 06-1903-2000, whereas coagulant TSP produce rubber SIR 20 with PRI values that are in accordance with standard, but the ash content above the standards set by the SNI.Keywords : latex, coagulant, SIR 20